Relação entre limitações físicas e sintomatologia depressiva em idosos europeus - Vicente, Francisco Freitas (2023)
Objetive: To explore the relationship between physical limitations and depressive symptomatology. Methods: Study with a cross-sectional design. Data were from the population-based Survey of Health, Aging, and Retirement in Europe (SHARE) wave seven (2017). Physical limitations were assessed by the Global Activity Limitations Indicator (GALI). The EURO-D scale was used to measure depressive symptomatology. Results: The sample consisted of 13450 individuals with a mean age of 70.7 ± 7.6 years. Physical limitations showed a positive and significant correlation with depressive symptomatology (r=0.221; p < 0.001). For men, having physical limitations increased 46% (OR=1.46, 95% IC: 1.35, 1.57) the probability of having depressive symptoms and for women increased 50% (OR=1.50, 95% IC: 1.38, 1.63). Conclusion: Having physical limitations increases the likelihood of having depressive symptomatology.